LOSS AND DAMAGE DUE TO CLIMATE CHANGE IN INDONESIA: AN OVERVIEW OF THE ASEAN COOPERATION ADAPTING TO GLOBAL WARMING - Sari, Diah Apriani Atika; Indriyani, Rachma (Indonesian Journal of International Law, 2015)
Climate change is already causing significant loss and damage, and this issue has only become more urgent. Indonesia as the biggest archipelagic state in the world has faced great challenge of loss and damage due to climate change. Moreover, Southeast Asia is highly vulnerable to climate change as a large proportion of the population and economic activity is concentrated along coastlines; the region is heavily reliant on agriculture for livelihoods; there is a high dependence on natural resources and forestry; and the level of extreme poverty remains high. Vulnerability differs between South East Asia’s countries, however they are not immune from the occurrence of bad impacts. For that reason, regional cooperation is essential to cope with climate change and its impacts. The United Nations Framework Convention on Climate Change (UNFCCC) has stated loss and damage as the actual and/or potential manifestation of impacts associated with climate change in developing countries that negatively affect human and natural systems. Future loss and damage is potentially of unimaginable magnitude. These associated loss and damage now require new approaches that must also consider the challenge of addressing non-economic losses. In 2009, an ASEAN Climate Change Initiative (ACCI) was created to enhance coordination and cooperation in addressing climate change. This article will presents an overview of strategy and mechanism on ACCI as loss and damage response, furthermore, what kind of prospect can be taken by Indonesia. Therefore, it will analyze how such regional cooperation are made possible to be a panacea for climate change problem.